AKTIVITAS ANTIOKSIDAN DAN ANTIFOOKSIDASI DARI EKSTRAK BUAH LABU KUNING (Cucurbita Moschata) [Antioksidan Activities And Antifotooxidation of Pumpkin (Cuurbita Moschata) Extracts] - Gumolung, Dokri; Suryanto, Edi; Mamuaja, Christin (Pascasarjana Unsrat, 2013)
The objective of this study were to identify carotenoid, phenolic contents, and to determine the free radical scavenging activiy, and active oxygen species on the skin, flesh, flakes and seeds of pumpkin.Active oxygen compound quenching effects was conducted using linoleic acid as substrate containing erythrosine as a sensitizer and exposed under continuous illumination (400 lux) with the fluorescent light for up to 15 hours. The results showed that all of the pumpkin parts containing beta-carotene and phenolic. All parts of the fruit had a free radical scavenging activity and activity oxygen species.Scavenging free radical activity of EET-Skin 78.85%, EET-Meat 62.16%, EET-tuft 74.74% and 78.28% EET-seed respectively were observed in this study. In the measurement of oxygen singlet activity stabilizer in the photooxidation of linoleic acid system for 15 hours, the amount of extract concentration significantly contribute to reduce the oxidation of linoleic fatty acid. The extract seeds from pumpkin was the most strongly inhibit the oxidation of linoleic fatty acid in the photooxidation. It can be concluded that pumpkin seeds extract had the most strongest free radical scavenging activity and active oxygen species.